The Role of Antibiotics in Childhood Diarrhea - Patil V D, Wali Rajshekar, Hiremath M. B., Metgud Tanmaya* (Recent Research in Science and Technology, 2010)
Abstract Acute diarrhoea is common illness in children. Diarrhea kills about four million people in developing countries each year. The development of oral therapy for the rehydration and maintenance of children with dehydrating diarrhea has become the worldwide mainstay of national diarrheal control programs. Antibiotics in management of diarrhoea though randomly used, are seldom indicated in children. This article mentions our experience in the treatment of acute diarrhoea in children without antibiotics. Keywords: Acute diarrhoea, Antibiotics